Analysing service quality on tourist satisfaction in Kampung Coklat Blitar - Saadillah, Dinu; Nadhirah, Aulia; Sookhai, Satesh (University of Islam Malang, 2024)
This study aims to analyze the influence of service quality dimensions on tourist satisfaction at Kampung Coklat agrotourism in Blitar Regency, East Java, Indonesia. As a popular agrotourism destination offering education on cocoa cultivation and chocolate processing, Kampung Coklat has significant potential to contribute to the local economy. However, gaps remain in the implementation of integrated and sustainable marketing strategies that align with tourist expectations. Using the ServQual model, this research applies multiple linear regression to measure the partial and simultaneous effects of five service quality dimensions—tangibles, responsiveness, empathy, reliability, and assurance—on tourist satisfaction. Data analysis shows that the service quality variables collectively explain 69.9% of the variation in tourist satisfaction, while the remaining 30.1% is attributed to external socio-economic factors such as income, education level, and household size. The t-test results indicate that empathy, reliability, and assurance significantly affect satisfaction, whereas tangibles and responsiveness do not have a significant impact when considered individually. The findings suggest that high-quality service, particularly in terms of emotional connection, trustworthiness, and staff competence, is essential to enhancing tourist experiences. Although limited by the scope of variables considered, this study offers valuable insights for agrotourism managers in designing strategies to improve service satisfaction and promote return visits.